Body, Terror, and Gender: The Representation of Women in Contemporary Indonesian Horror Films - Prasetyo, Dwi; Saraswati, Tia; Bah, Yahya Muhammed (Journal of Social Dynamics and Governance, 2025)
This article analyzed the representation of the female body in contemporary Indonesian horror films by drawing on feminist film theory and cultural studies frameworks. Focusing on four key films released between 2017 and 2020, Pengabdi Setan, Sebelum Iblis Menjemput, Kuntilanak, and Impetigore, the study examined how terror was constructed through visual, narrative, and symbolic strategies shaped by gender perspectives. Using a qualitative approach that combined textual and semiotic analysis, the findings revealed that the female body was portrayed ambivalently: both as a victim and as a source of power, referencing the concept of the monstrous-feminine. These representations were mediated through aesthetic techniques—such as camera angles, sound design, and lighting that shaped cultural meanings related to motherhood, sexuality, and social taboos. The study revealed that Indonesian horror films drew on local myths, spiritual beliefs, and socioreligious tensions to produce a distinctly Indonesian variant of the monstrous-feminine, which differed from its Western counterparts. While some films reproduced patriarchal norms by punishing transgressive female characters, others offered subversive narratives that positioned women as agents of revenge and resistance. This study contributed to global feminist film discourse by foregrounding the Southeast Asian context and highlighted the role of the horror genre in expressing contemporary cultural anxieties surrounding gender and the body in Indonesia.